Padrão espacial e temporal no investimento reprodutivo em aranhas doadoras de presentes nupciais do gênero Paratrechalea Carico, 2005 (Araneae, Trechaleidae) - Spindler, Claudia Sabrina (Universidade do Vale do Rio dos Sinos, 2015)
The reproductive success of an individual is optimized following trade-off constraints among its life-history components, where the decision to invest into reproduction or maintenance is influenced by selective pressures that defines the direction and intensity of sexual selection. Nuptial feeding represents a reproductive investment by the males, and the fate of an edible item in terms of consumption (physiological maintenance), or reproduction are defined by ecological factor and by the animals’ physiological condition. The main goal of this dissertation was to investigate how such decisions varies along the reproductive season of a population. Based on a field sample procedure, I investigated how males from two spider species from the Paratrechalea Carico, 2005 genus adjust their investments in nuptial feeding along their reproductive season, observing the consequences of such investment in terms of males’ habitat dispersion in relation to other adult categories, and in terms of the occurrence of alternative strategies regarding the nuptial feeding quality. There is a spatial segregation defined by the amount of reproductive investment for both males and females, where males during mate search and females during maternal care shared the same areas. I interpreted this pattern as an adaptive reaction by the non-receptive females in order to gain an extra source of energy, leading to energetic and reproductive costs for the males by wasting their nuptial gifts in a non-sexual interaction. Regarding the nuptial feeding investment along the reproductive season, the probability of occurrence of a high quality nuptial gift (nutritive gifts) showed strong fluctuations along the season, but such changes were not related to an expected pattern of terminal investment. However, the investment rules regarding low quality nuptial gifts (token gifts) were constant over time, corroborating the hypothesis that deceptive gifts constitutes an alternative strategy for those species.
Keywords: Alimentação nupcial; Condição corporal; Conflito sexual; Investimento reprodutivo; Seleção sexual; Body condition; Nuptial feeding; Reproductive investment; Sexual selection; Sexual conflict; ACCNPQ::Ciências Biológicas::Biologia Geral